Pendidikan Inklusif dan Multikultur dalam Perspektif Hadis Nabi Saw - Moh Toriqul Chaer (Cendekia: Kependidikan dan Kemasyarakatan, 2016)
The study of the association or social interaction in Islamic education serves as the urgent problembecausea good social interaction is likely to affectstudents’ good behavior in a pluralistic society and religious culture. Students’ understanding of this substance has become a very important resource in instilling the inclusive and multicultural education. This article presented and examined the hadiths which were relevant to Islamic educational materialsregarding the instructional issues of social interaction, tolerance, and cooperation such as Muamalah rights and Islamic preaching. The study revealed that the hadiths related to social interaction with non-Muslims had notrecommended to be rude to the non-Muslims if they did not hurt and harm the Muslims. This is consistent with the meaning of Islam itself that is to save and is not to be a device that punishthe people who do not believe in Allah, and Islam should be the spirit of unlimited ocean full of love who is able to frame the diversity in Indonesia.إن دراسة الصلة الاجتماعية في عالم التربية الإسلامية مهمة، لأن الصلة الاجتماعية الطيّبة  تؤدّى إلى السلوك الحسن للطلاب في المجتمع المتعدد الثقافات والأديان. وإن فهم الطلاب لهذه أصبح مادة مهمة  في ضوء غرس قيم التربية الشاملة  والمتعددة الثقافات. حاولت هذه المقالة عرض الأحاديث المناسبة بمواد التربية الإسلامية المتعلقة بالاتصال الاجتماعي والتسامح والتعاون، مثل الأحاديث عن حقوق المعاملة والدعوة الإسلامية.  وثمة أحاديث متعلقة بالاتصال الاجتماعي بغير المسلمين, وأشارت الأحاديث إلى أنّه ليس هناك حثّ على إيذاء غير المسلمين إذا كانوا لا يؤذين المسلمين ولا يضرّونهم. وهذا كما يوجد في معنى الإسلام (المنجّي) وليس جهازا لتحكيم جميع الناس الذين لا يؤمنون به، وهو يكون ناشرا لروح المحبّة لجميع الناس في ضوء التعدّدات في إندونيسيا.